Upaya Identifikasi Perilaku Safety Driving Pada Pengemudi Aggressive Driving - Riza Phahlevi; Rizka Amanda Choirani; Siti Shofiah (Universitas Medan Area, 2023)
Surveys were carried out on efforts to identify safe driving behavior for drivers using the Pejagan - Pemalang toll road. This is done to determine patterns of driving behavior, especially to identify the effect of understanding safe driving on aggressive driving behavior. The research method used is a quantitative descriptive method with accidental sampling with the independent variable safe driving and the dependent variable aggressive driving. The roughness value for the Pejagan – Pemalang toll road was obtained > 0.33 µm and the unevenness value was 4.95, Tegal access. Data on maximum speed (v) and 85th percentile speed for class I vehicles, i.e. 166.09 km/hour and 115.68 km/hour. Out of 100 respondents, 77% of respondents understood safe driving, but in driving behavior 89% showed aggressive driving behavior. This means that it is necessary to practice safe driving behavior, especially when going through the toll road. From the results of the interviews, it was found that the stretches of toll roads are monotonous, silent, and to overcome drowsiness are the reasons for drivers to drive above 100 km/hour, which shows that the driver is behaving aggressive when driving.